Development of unified classifier of special terrain maps using geoinformation technologies - Cherenko, Aliaksei S. (Journal of the Belarusian State University. Geography and Geology, 2022)
A method for creating a unified classifier of special terrain maps using geoinformation technologies is presented. The existing classifiers of maps of the operational and tactical situation, special and topographic terrain maps used in the Armed Forces of the Republic of Belarus are analysed. Using the software products of the design bureau «Panorama», a methodology of developing new classifiers for geoinformation and traditional approaches is described. The urgency of creating the first unified digital classifier of special terrain maps for the geoinformation approach, which contains all available special terrain maps and allow you to use them in conjunction with maps of the operational-tactical situation and electronic topographic terrain maps crosslinking, is substantiated. The relevance of the creation of digital classifiers of special terrain maps by scale for the traditional approach involving the development of maps for analog printing is substantiated. In the created digital classifiers, for the first time, a system of classification and coding of terrain objects was used for them, which is based on the hierarchical method of classification of information of the first subset and the faceted method of classification of information of the second subset. The developed classifiers have a unified colour palette and cartographic fonts. Examples of the created symbols of the classifiers of special terrain maps are given. It is concluded that it is necessary to use the developed unified classifier of special terrain maps in the Armed Forces of the Republic of Belarus.
Keywords: digital maps; geoinformation technologies; special terrain maps; vector map classifier; symbols; object coding